Brazilian Peppertree Thrips Pseudophilothrips ichini (Hood) (Insecta: Thysanoptera: Phlaeothripidae) - Patricia Prade; Carey R Minteer; James P Cuda (EDIS, 2020)
The Brazilian peppertree thrips, Pseudophilothrips ichini (Hood) (Thysanoptera: Phlaeothripidae), is an insect native to Brazil (Figure 1). This species has been studied for the last 20+ years as a potential biological control agent of Brazilian peppertree, Schinus terebinthifolia Raddi (Sapindales: Anacardiaceae), in Florida (Cuda et al. 2008; Cuda et al. 2008; Manrique at al. 2014; Wheeler et al. 2016a, b). Host specificity experiments demonstrated that Pseudophilothrips ichini has a limited host range (Cuda et al. 2008; Cuda et al. 2009; Wheeler et al. 2017) and can cause a severe reduction of Brazilian peppertree biomass (Manrique at al. 2014). https://edis.ifas.ufl.edu/in1270